Nonaqueous electrolyte electricity storage element

By using the positive electrode active material containing tungsten elements and the negative electrode active material with carbon covered solid graphite in the nonaqueous electrolyte storage element, the problem of capacity reduction in high temperature environment is solved, and a larger post-storage capacity and a longer service life are achieved.

CN119631197APending Publication Date: 2025-03-14GS YUASA INT LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057111.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-07-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The capacity of existing nonaqueous electrolyte storage components is easily reduced after being stored in a high temperature environment.

Method used

The positive electrode active material containing tungsten element and carbon-covered solid graphite were used as the negative electrode active material, and the carbon coating amount was 12.0 mass % or more and the porosity was 2% or less to suppress the precipitation of tungsten element and the decomposition of the nonaqueous electrolyte.

Benefits of technology

The storage capacity of nonaqueous electrolyte storage components is significantly increased under high temperature environments and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631197A_ABST
    Figure CN119631197A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte electricity storage element according to one aspect of the present invention is provided with a positive electrode containing a positive electrode active material containing elemental tungsten, and a negative electrode containing a carbon-coated solid graphite in which at least a portion of the surface of the solid graphite is coated with a carbonaceous material other than graphite, the porosity of the carbon-coated solid graphite being 2% or less, and the porosity of the carbon-coated solid graphite being 2% or less. The amount of the carbonaceous material coated in the carbon-coated solid graphite is 12.0 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-aqueous electrolyte storage element. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by the transfer of charge transfer ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.

[0003] The positive electrode active material for non-aqueous electrolyte storage element uses lithium transition metal composite oxides, polyanion compounds, etc. In order to improve the performance of non-aqueous electrolyte storage element, the surface of the particles of positive electrode active material is also coated with other compounds. Patent document 1 records the positive electrode material for lithium secondary battery formed by coating the surface of particles of lithium manganese composite oxide with metal oxides such as titanium oxide and tin oxide. On the other hand, carbon materials headed by graphite are widely used as negative electrode active materials (refer to patent document 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-6676

[0007] Patent Document 2: Japanese Patent Application Publication No. 2005-222933 Summary of the invention

[0008] It is desired that the capacity of a nonaqueous electrolyte storage device does not easily decrease even after storage in a high-temperature environment.

[0009] An object of the present invention is to provide a non-aqueous electrolyte storage element having a large capacity after storage in a high temperature environment.

[0010] A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode and a negative electrode, wherein the positive electrode comprises a positive electrode active material containing a tungsten element, and the negative electrode comprises carbon-coated solid graphite in which at least a portion of the surface of the solid graphite is coated with a carbonaceous material other than graphite, the porosity of the carbon-coated solid graphite being less than 2%, and the coating amount of the carbonaceous material in the carbon-coated solid graphite being greater than 12.0 mass %.

[0011] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte storage element having a large capacity after storage in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.

[0013] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION

[0014] First, the outline of the nonaqueous electrolyte energy storage device disclosed in this specification will be described.

[0015] [1]: A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode and a negative electrode, wherein the positive electrode comprises a positive electrode active material containing a tungsten element, and the negative electrode comprises a carbon-coated solid graphite in which at least a portion of the surface of the solid graphite is coated with a carbonaceous material other than graphite, wherein the porosity of the carbon-coated solid graphite is less than 2%, and the coating amount of the carbonaceous material in the carbon-coated solid graphite is greater than 12.0% by mass.

[0016] The non-aqueous electrolyte storage element described in [1] above has a large capacity after being stored in a high temperature environment. The reason is not clear, but it is speculated to be the following. By using a positive electrode active material containing tungsten, the initial output of the non-aqueous electrolyte storage element becomes larger. However, when the non-aqueous electrolyte storage element is stored in a high temperature environment, the tungsten element contained in the positive electrode active material dissolves into the non-aqueous electrolyte. The inventors of the present invention have found that the dissolved tungsten element is precipitated on the negative electrode active material, and the tungsten element precipitated on the surface of the negative electrode active material (in the case where the negative electrode active material is graphite, in particular, the edge surface of the graphite crystal and the surface of the internal voids of the graphite particles) reacts with the non-aqueous electrolyte, thereby decomposing the non-aqueous electrolyte, and there is a risk of reducing the capacity of the non-aqueous electrolyte storage element.

[0017] In contrast, according to the non-aqueous electrolyte storage element described in [1] above, by using solid graphite with few internal voids in graphite particles as the negative electrode active material, the tungsten element dissolved from the positive electrode active material is suppressed from precipitating on the surface of the internal voids of the graphite particles. Furthermore, by coating at least a portion of the surface of the solid graphite with a carbonaceous material other than graphite and making the coating amount of the carbonaceous material greater than 12.0% by mass, the edge faces of the graphite crystals in the solid graphite can be appropriately covered with the above-mentioned carbonaceous material, and the precipitation of tungsten elements on the edge faces of the above-mentioned graphite crystals can be suppressed. As a result, the decomposition reaction of the non-aqueous electrolyte in the internal voids of the graphite particles and the edge faces of the graphite crystals in the solid graphite is less likely to occur. It is speculated that this helps to increase the capacity of the non-aqueous electrolyte storage element described in [1] above after storage in a high temperature environment.

[0018] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge or discharge or in the discharged state. 002 ) is a carbon material with a size of 0.33 nm or more and less than 0.34 nm.

[0019] Here, the "discharge state" of a carbon material such as graphite refers to a discharge state in which charge transport ions such as lithium ions that can be absorbed and released during charge and discharge are fully released from the carbon material as the negative electrode active material. For example, in a half-cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic lithium (Li) as a counter electrode, a state in which the open circuit voltage is 0.6 V or more is a typical example of the "discharge state" of the carbon material.

[0020] The "solid" in solid graphite means that the inside of the graphite particle is full and there are substantially no voids. More specifically, "solid" means that in the SEM image obtained using a scanning electron microscope (SEM), in the cross section of the observed particle, the area ratio (void ratio) of the voids in the particle relative to the area of ​​the entire particle is 2% or less.

[0021] The "area ratio of voids within the particle to the area of ​​the entire particle (void ratio)" in the graphite particle can be determined by the following procedure.

[0022] (1) Preparation of test samples

[0023] The negative electrode to be measured was fixed with a thermosetting resin. The cross section of the negative electrode fixed with the resin was exposed by ion milling to prepare a sample for measurement. It should be noted that the negative electrode to be measured was prepared by the following steps. The non-aqueous electrolyte storage element was discharged at a constant current of 0.1C to the discharge end voltage during normal use to obtain a discharged state. The non-aqueous electrolyte storage element in the discharged state was disassembled and the negative electrode was taken out. A half-cell was assembled using the taken out negative electrode as the working electrode and metal Li as the counter electrode. When the open circuit voltage of the half-cell was less than 0.6V, the half-cell was discharged in a manner that the open circuit voltage was 0.6V or more. It should be noted that the discharge in the above-mentioned half-cell refers to an oxidation reaction that releases charge transfer ions from graphite as the negative electrode active material. The half-cell was disassembled, the negative electrode was taken out, and it was fully washed with dimethyl carbonate, and then dried under reduced pressure at room temperature for 24 hours. The operation from disassembly of the non-aqueous electrolyte storage element to preparation of the negative electrode to be measured was performed in a dry air atmosphere with a dew point of less than -40°C. Here, the term "normal use" refers to a case where the nonaqueous electrolyte electricity storage element is used under the charge and discharge conditions recommended or specified for the nonaqueous electrolyte electricity storage element.

[0024] (2) Acquisition of SEM images

[0025] In order to obtain the SEM image, a JSM-7001F (manufactured by JEOL Ltd.) was used as a scanning electron microscope. The SEM image was set to observe the secondary electron image. The acceleration voltage was set to 15 kV. The observation magnification was set to a magnification at which the number of graphite particles appearing in one field of view was more than 3 and less than 15. The obtained SEM image was saved as an image file. In addition, various conditions such as the spot diameter, operating distance, irradiation current, brightness, and focus were appropriately set in such a way that the outline of the graphite particles became clear.

[0026] (3) Shearing of graphite particle contours

[0027] The contour of the graphite particles was cut from the acquired SEM image using the image cutting function of the image editing software Adobe Photoshop Elements 11. The contour cutting was performed by selecting the outer side of the contour of the graphite particles using the quick selection tool and editing the portion outside the graphite particles to a black background. At this time, when the number of graphite particles whose contours could be cut was less than 3, the SEM image was acquired again until the number of graphite particles whose contours could be cut reached 3 or more.

[0028] (4) Binarization

[0029] The image of the first graphite particle among the cut graphite particles was binarized using the image analysis software PopImaging 6.00, with a concentration 20% lower than the concentration at the maximum intensity set as a threshold. The area on the high concentration side was calculated using the binarization process and was set as the "area S1 of the voids in the particle".

[0030] Next, the same first graphite particle image as before was binarized with a concentration of 10% as a threshold value. The outer edge of the graphite particle was determined by binarization, and the area inside the outer edge was calculated to be the "area S0 of the entire particle".

[0031] The ratio of S1 to S0 (S1 / S0) is calculated using S1 and S0 calculated above, thereby calculating the "area ratio R1 of the voids within the particle to the area of ​​the entire particle" of the first graphite particle.

[0032] The above binarization process is also performed on the images of the second and subsequent graphite particles among the cut graphite particles to calculate the area S1 and the area S0. Based on the calculated area S1 and the area S0, the area ratios R2, R3, etc. of the voids of each graphite particle are calculated.

[0033] (5) Determination of the area ratio of voids

[0034] By calculating the average value of the area ratios R1, R2, R3, ... of all the voids calculated by the binarization process, the "area ratio of the voids in the particle to the area of ​​the entire particle (void ratio)" is determined.

[0035] It should be noted that instead of the scanning electron microscope used for the above-mentioned "acquisition of SEM image", the image editing software used for the "cutting of the outline of graphite particles", and the image analysis software used for the "binarization processing", devices and software capable of performing equivalent measurements, image editing and image analysis can be used.

[0036] [2]: In the non-aqueous electrolyte storage element described in [1] above, the carbonaceous material may be non-graphite carbon. The non-aqueous electrolyte storage element described in [2] above can further reduce the decrease in capacity after storage in a high temperature environment by virtue of the carbonaceous material being non-graphite carbon. “Non-graphite carbon” refers to a carbonaceous material that is not “graphite”.

[0037] [3]: In the non-aqueous electrolyte storage element described in [1] or [2] above, the solid graphite may be solid natural graphite. Natural graphite has a higher crystallinity than artificial graphite. Therefore, when the solid graphite is solid natural graphite, the discharge capacity per unit mass of the negative electrode active material of the non-aqueous electrolyte storage element described in [3] above becomes larger, and the capacity of the non-aqueous electrolyte storage element after storage in a high temperature environment also becomes larger.

[0038] [4]: In the nonaqueous electrolyte storage element described in any one of [1] to [3] above, the positive electrode active material may further contain a transition metal element other than the tungsten element and a lithium element, and the content of the tungsten element in the positive electrode active material relative to the metal element other than the tungsten element and the lithium element may be 0.2 mol% or more. Since the nonaqueous electrolyte storage element described in [4] above contains a sufficient amount of tungsten element in the positive electrode active material, the initial output and capacity of the nonaqueous electrolyte storage element become large. In addition, when the positive electrode active material contains such a high concentration of tungsten element, by using it in combination with a negative electrode comprising solid graphite coated with a specific amount of carbonaceous material, the edge surfaces of the graphite crystals of the solid graphite are appropriately coated with the carbonaceous material, thereby further increasing the capacity of the nonaqueous electrolyte storage element after storage in a high temperature environment.

[0039] In the present invention, "the content of tungsten element in the positive electrode active material relative to metal elements other than tungsten element and lithium element" refers to the ratio (molar %) of the amount (mole) of tungsten element contained in the positive electrode active material relative to the total amount (mole) of all metal elements other than tungsten element and lithium element.

[0040] The amount of tungsten in the positive electrode active material and the total amount of all metal elements other than tungsten and lithium were determined according to the following steps. First, the non-aqueous electrolyte storage element was discharged at a constant current of 0.05C to the lower limit voltage during normal use. The positive electrode was removed and a test cell with metal Li as the counter electrode was assembled. The positive electrode was discharged at a constant current of 10 mA per 1g of positive electrode active material until the positive electrode potential reached 3.0 V vs. Li / Li. + , adjust the positive electrode to a fully discharged state. Disassemble again and take out the positive electrode. Use dimethyl carbonate to thoroughly clean the components (electrolyte, etc.) attached to the taken out positive electrode, and after drying under reduced pressure at room temperature for 24 hours, take out the positive electrode active material. The operation from disassembly of the non-aqueous electrolyte storage element to taking out the positive electrode active material for measurement is carried out in an argon atmosphere with a dew point below -60°C. The positive electrode active material taken by the above method is completely dissolved in an acid that can dissolve tungsten and the positive electrode active material by microwave decomposition. Next, the solution is diluted to a certain amount with pure water as a measurement solution. Then, using a polytype high-frequency inductively coupled plasma emission spectrometer ICPE-9820 (manufactured by Shimadzu Corporation), the concentration of all metal elements contained in the positive electrode active material containing tungsten and lithium elements in the above measurement solution is measured by high-frequency inductively coupled plasma emission spectrometry (ICP). The amount of tungsten in the positive electrode active material and the total amount of all metal elements other than tungsten and lithium are quantified from the obtained concentrations of tungsten, lithium, and all metal elements other than tungsten and lithium. It should be noted that in the calculation of the concentrations of tungsten, lithium, and all metal elements other than tungsten and lithium in the measurement solution, for example, a calibration curve method can be used to prepare a calibration curve from a solution of known concentration of each element and calculate the concentration of each element in the measurement solution.

[0041] [5]: In the non-aqueous electrolyte storage element described in any one of [1] to [4] above, the average particle size of the solid graphite may be 5 μm or more. When solid graphite with a large particle size is used, the surface area of ​​the solid graphite becomes smaller. As a result, the non-aqueous electrolyte storage element described in [5] above is less likely to precipitate tungsten on the surface of the solid graphite particles, and the capacity of the non-aqueous electrolyte storage element after storage in a high temperature environment becomes larger.

[0042] The “average particle size” refers to a value at 50% of the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) based on a particle size distribution measured by a laser diffraction / scattering method using a solution obtained by diluting particles in a solvent in accordance with JIS-Z-8825 (2013).

[0043] The structure of a non-aqueous electrolyte storage element according to one embodiment of the present invention, the structure of a storage device, and a method for manufacturing a non-aqueous electrolyte storage element, as well as other embodiments, are described in detail. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.

[0044] <Structure of non-aqueous electrolyte energy storage device>

[0045] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator; a nonaqueous electrolyte; and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is generally a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state in which they are stacked via a separator. The nonaqueous electrolyte exists in a state impregnated in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") is described.

[0046] (positive electrode)

[0047] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0048] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by the volume resistivity 10 measured in accordance with JIS-H-0505 (1970). -2 Ω·cm is the threshold value for judgment. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.

[0049] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased, and the energy density per unit volume of the non-aqueous electrolyte storage element can be increased.

[0050] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.

[0051] The positive electrode active material layer contains a positive electrode active material and may contain any component such as a conductive agent, a binder, a thickener, and a filler as required.

[0052] The positive electrode active material contains tungsten. The tungsten element can exist in the form of a compound such as an oxide (WO3). The compound containing the tungsten element can, for example, be coated with at least a portion of the surface of particles of a substance capable of absorbing and releasing charge transport ions such as lithium ions. In other words, the positive electrode active material can include a substance capable of absorbing and releasing charge transport ions and a compound containing the tungsten element. The positive electrode active material can essentially consist only of a substance capable of absorbing and releasing charge transport ions and a compound containing the tungsten element. The substance capable of absorbing and releasing charge transport ions itself can contain tungsten (that is, tungsten can be dissolved in the positive electrode active material). The tungsten element can, for example, exist on the surface of particles of the positive electrode active material. The tungsten element can exist inside the particles of the positive electrode active material. In this way, by containing tungsten in the positive electrode active material, side reactions in the positive electrode can be suppressed, the conductivity of charge transport ions such as lithium ions can be improved, and the output and capacity of the non-aqueous electrolyte storage element can be improved. As a form of containing tungsten in the positive electrode active material, there is a method of coating a compound containing tungsten on the surface of particles of a substance capable of absorbing and releasing charge transport ions. In addition, there is also a method in which a compound containing tungsten is carried on the particle surface of the positive electrode material or contained in the particle by adding tungsten element and calcining it when synthesizing a substance capable of absorbing and releasing charge transfer ions. As the positive electrode active material containing tungsten element, a commercially available product can be used.

[0053] As a substance capable of absorbing and releasing charge transport ions, a substance capable of absorbing and releasing lithium ions is preferred, and these can use materials that are known in the past. Examples of such substances include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanionic compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co(1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. The atoms or polyanions in these materials can be partially replaced by atoms or anions composed of other elements. These materials can be coated with other materials on the surface. In the positive electrode active material layer, one of these materials can be used alone, or two or more can be mixed and used.

[0054] As the material capable of absorbing and releasing charge transport ions, lithium transition metal composite oxides are preferred, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure are more preferred, and Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). In the above Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2, for example, preferably 0.1≤γ<0.9, 0.1≤β<0.9. When such a substance is used, the effect of increasing the output and capacity of the non-aqueous electrolyte storage element by the tungsten element is particularly fully exerted.

[0055] As a substance capable of absorbing and releasing charge transfer ions, in the case of using lithium transition metal composite oxides, polyanionic compounds, etc., the positive electrode active material further contains transition metal elements other than tungsten. In the case where the positive electrode active material further contains transition metal elements other than tungsten and lithium elements, the content of tungsten in the positive electrode active material relative to the metal elements other than tungsten and lithium elements is preferably 0.2 mol% to 3 mol%, and more preferably 0.5 mol% to 2 mol%. By making the content of tungsten element above the above lower limit, the effect brought by tungsten element in the positive electrode active material can be fully played, and the output of the non-aqueous electrolyte storage element can be further increased. On the other hand, by making the content of tungsten element below the above upper limit, the dissolution of tungsten element from the positive electrode active material can be easily suppressed, and the capacity reduction after storage in a high temperature environment can be further reduced.

[0056] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By making the content of the positive electrode active material within the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0057] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm to 20 μm. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is used as the average particle size of the positive electrode active material.

[0058] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. When pulverizing, wet pulverization in which water or a non-aqueous solvent such as hexane coexists can also be used. As a classification method, a sieve, a wind classifier, etc. can be used together with a dry method or a wet method as needed.

[0059] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be mentioned. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be mentioned. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be mentioned. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be mentioned. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be mentioned. As the shape of the conductive agent, powder, fiber, etc. can be mentioned. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in a composite. For example, a material obtained by composite carbon black and CNT can be used. Among them, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.

[0060] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the nonaqueous electrolyte storage device can be increased.

[0061] Examples of adhesives include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0062] The content of the binder in the positive electrode active material layer is preferably 1% by mass to 10% by mass, and more preferably 3% by mass to 9% by mass. When the content of the binder is within the above range, the positive electrode active material can be stably retained.

[0063] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.

[0064] The content of the thickener in the positive electrode active material layer may be, for example, 0.1% to 6% by mass, or 0.5% to 3% by mass. The content of the thickener in the positive electrode active material layer may be 1% by mass or less, or the positive electrode active material layer may not contain the thickener.

[0065] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene; inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; carbonates such as calcium carbonate; poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate; nitrides such as aluminum nitride and silicon nitride; and mineral resources such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or their artificial products.

[0066] The content of the filler in the positive electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the positive electrode active material layer may be 3% by mass or less, or 1% by mass or less, or the positive electrode active material layer may not contain any filler.

[0067] The mass per unit area of ​​the positive electrode active material layer is not particularly limited, and may be, for example, 4.0 mg / cm 2 ~15.0mg / cm 2 The lower limit of the mass per unit area of ​​the positive electrode active material layer is preferably 4.5 mg / cm 2 , more preferably 4.8 mg / cm 2 or 5.0mg / cm 2 In some embodiments, the mass per unit area of ​​the positive electrode active material layer may be, for example, 5.5 mg / cm 2 Above, it can also be 5.8mg / cm 2 The upper limit of the mass per unit area of ​​the positive electrode active material layer is preferably 12.0 mg / cm 2 , more preferably 10.0 mg / cm 2 . In a non-aqueous electrolyte storage element having a positive electrode active material layer whose mass per unit area is within the above range, the application effect of the present configuration can be more appropriately exerted. The "mass per unit area of ​​the positive electrode active material layer" refers to the mass per unit area of ​​one positive electrode active material layer. For example, in a case where the positive electrode has a positive electrode substrate and positive electrode active material layers are respectively provided on both sides of the positive electrode substrate, the "mass per unit area of ​​the positive electrode active material layer" is the mass per unit area of ​​the positive electrode active material layer on one side of the positive electrode substrate. The same applies to the "mass per unit area of ​​the negative electrode active material layer" described later.

[0068] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0069] (negative electrode)

[0070] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the positive electrode described above.

[0071] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, or their alloys, carbonaceous materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.

[0072] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the non-aqueous electrolyte storage element can be increased.

[0073] The negative electrode active material layer contains a negative electrode active material and may contain any component such as a conductive agent, a binder, a thickener, and a filler as required.

[0074] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0075] The negative electrode active material includes carbon-coated solid graphite. In the carbon-coated solid graphite, at least a portion of the surface of the solid graphite is coated with a carbonaceous material other than graphite. By including solid graphite in the negative electrode active material, the precipitation of tungsten elements on the surface of the internal voids of the graphite particles can be suppressed. Furthermore, by using carbon-coated solid graphite whose surface is at least partially coated with a carbonaceous material other than graphite as solid graphite, the precipitation of tungsten elements on the edge surfaces of graphite crystals in the solid graphite can be suppressed. Therefore, the capacity of the non-aqueous electrolyte storage element after storage in a high temperature environment becomes larger.

[0076] In the cross section of the solid graphite observed in the above SEM image, the area ratio (void ratio) of the voids in the particle relative to the area of ​​the entire particle is 2% or less, more preferably 1% or less, and further preferably 0.5% or less. The lower limit of the area ratio (void ratio) may be 0%.

[0077] The solid graphite may be natural graphite or artificial graphite, preferably natural graphite. When the solid graphite is natural graphite (solid natural graphite), the discharge capacity per unit mass of the negative electrode active material becomes larger, and the capacity after storage in a high temperature environment also becomes larger.

[0078] Natural graphite is a general term for graphite extracted from natural resources. The shape of solid natural graphite is not particularly limited, and examples thereof include flaky graphite, blocky graphite (flaky graphite), and earthy graphite. Solid natural graphite may also be spheroidized natural graphite particles obtained by spheroidizing flaky natural graphite and the like. Natural graphite may also be a substance in which four peaks appear in the range of 40° to 50° at a diffraction angle 2θ in an X-ray diffraction pattern using CuKα rays measured before charge and discharge or in a discharge state. These four peaks are considered to be two peaks from a hexagonal crystal structure and two peaks from a rhombohedral crystal structure. In the case of artificial graphite, it is generally believed that only two peaks from a hexagonal crystal structure appear. In the X-ray diffraction pattern, the ratio of the peak intensity from the (012) plane to the peak intensity from the (100) plane ((012) / (100)) is preferably 0.3 or more, and more preferably 0.4 or more. The peak intensity ratio ((012) / (100)) is preferably 0.6 or less. Here, the (100) plane is derived from a hexagonal crystal structure, and the (012) plane is derived from a rhombohedral crystal structure.

[0079] The average particle size of solid graphite can be, for example, 1 μm to 25 μm, preferably 3 μm to 20 μm, more preferably 5 μm to 15 μm, and further preferably 7 μm to 13 μm. In some embodiments, the average particle size of solid graphite can be 8 μm to 12 μm, or even more than 9 μm. By having the average particle size of solid graphite in the above range, the charge and discharge performance of the non-aqueous electrolyte storage element can be improved. In particular, when the average particle size of solid graphite is above the above lower limit, the capacity after storage in a high temperature environment becomes larger. In order to obtain solid graphite with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected, for example, from the methods exemplified above for the positive electrode.

[0080] As the carbonaceous material coating the solid graphite, non-graphite carbon is preferred. By using the carbonaceous material as non-graphite carbon, the capacity after storage in a high temperature environment can be further increased. Examples of non-graphite carbon include difficult-to-graphitize carbon (hard carbon), easy-to-graphitize carbon (soft carbon), and amorphous carbon (amorphous carbon). "Difficult-to-graphitize carbon" refers to the above-mentioned d 002 d is a carbon material with a diameter of 0.36 nm to 0.42 nm. Examples of the non-graphitizable carbon include phenolic resin sintered products, furan resin sintered products, furfuryl alcohol resin sintered products, and the like. "Easily graphitizable carbon" refers to the carbon material with a diameter of 0.36 nm to 0.42 nm. 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm. Examples of graphitizable carbon include coke and pyrolytic carbon. 002 A carbon material having a diameter exceeding 0.42 nm or a carbon material having no long-range ordered crystal structure (typically, a carbon material in which no peak attributed to the (002) plane is observed in X-ray diffraction measurement).

[0081] As the lower limit of the coating amount of the above-mentioned carbonaceous material in the above-mentioned carbon-coated solid graphite (the ratio of the mass of the carbonaceous material to the total mass of the solid graphite and the carbonaceous material coating the solid graphite), it is 12.0 mass %, preferably 12.5 mass %. In some ways, the lower limit of the coating amount of the above-mentioned carbonaceous material can be 12.8 mass %, or 13.0 mass %. By the coating amount of the above-mentioned carbonaceous material being above the above-mentioned lower limit, it is possible to suppress the precipitation of the edge surface of the graphite crystal of the tungsten element in the solid graphite, and increase the capacity after preservation under a high temperature environment. On the other hand, as the upper limit of the coating amount of the above-mentioned carbonaceous material, it is not particularly limited, preferably 30 mass %, and sometimes more preferably 25 mass %. In some ways, the upper limit of the coating amount of the above-mentioned carbonaceous material can be 20 mass %, or 15 mass % (for example, less than 15 mass %, less than 14.8 mass %, less than 14.5 mass %). If the coating amount of the above-mentioned carbonaceous material is too large, sometimes the performance improvement effect brought about by the coating of the above-mentioned carbonaceous material (for example, the effect of increasing the capacity after preservation under a high temperature environment) tends to be passivated. The coating amount of the carbonaceous material in the carbon-coated solid graphite may be within any of the lower limits described above to any of the upper limits described above.

[0082] The coating amount of the above-mentioned carbonaceous material is measured as follows. That is, using a thermogravimetric differential thermal (TG / DTA) analyzer, in a water vapor atmosphere with a humidity of 65% RH, the temperature is raised from room temperature to 1200°C at a heating rate of 5°C / min, and the thermogravimetric curve of the carbon-coated solid graphite is measured (horizontal axis: temperature, vertical axis: mass of the carbon-coated solid graphite). In the thermogravimetric curve, the mass decreases with the increase in temperature, but initially the mass decreases at around 100°C, which is equivalent to the water adsorbed on the solid graphite. Then, the carbonaceous material coated on the solid graphite decomposes, thereby reducing the mass equivalent to the carbonaceous material, and then, the solid graphite as the base material decomposes, thereby reducing the mass equivalent to the solid graphite. Therefore, in the obtained thermogravimetric curve, the mass of the carbon-coated solid graphite after the mass reduction corresponding to the amount of water adsorbed to the solid graphite at around 100°C is taken as a reference (100%), and the ratio of the mass reduction from the reference to the decomposition start temperature of the solid graphite (=[mass reduction from the above reference to the decomposition start temperature of the solid graphite / mass of the carbon-coated solid graphite in the above reference] × 100) is taken as the coating amount of the above carbonaceous material. The above thermogravimetric curve is typically divided into (1) a first region where the mass change is almost non-existent after the mass reduction corresponding to the amount of water adsorbed to the solid graphite at around 100°C with temperature increase, (2) a second region where the mass of the carbonaceous material of the carbon-coated solid graphite is rapidly reduced after the above first region, (3) a third region where the mass is slowly reduced or almost non-reduced after the above second region, and (4) a fourth region where the mass of the solid graphite is rapidly reduced after the above third region. The temperature at which the bending point (the measuring point of the change in the inclination of the curve) produced during the process of transitioning from the third region of (3) to the fourth region of (4) is observed is a typical example of the decomposition start temperature of solid graphite mentioned here. The decomposition start temperature of solid graphite is determined by the intersection of the approximate straight line of the curve of the process of (3) and the approximate straight line of the curve indicating a sharp mass reduction in the process of (4). The decomposition start temperature of solid graphite can be above about 950°C (for example, 950°C to 1000°C in the case of natural graphite and 980°C to 1100°C in the case of artificial graphite).

[0083] The content of carbon-coated solid graphite in the negative electrode active material layer is preferably 60% to 99.5% by mass, and more preferably 90% to 99% by mass. By making the content of carbon-coated solid graphite within the above range, high energy density and manufacturability of the negative electrode active material layer can be achieved, and the capacity after storage in a high temperature environment can be further increased.

[0084] The negative electrode active material may include other negative electrode active materials other than carbon-coated solid graphite. As other negative electrode active materials, hollow graphite (graphite other than carbon-coated solid graphite) and other various negative electrode active materials known in the past can be used. Among them, carbon-coated solid graphite is preferably used as the main negative electrode active material. For example, in the cross-sectional SEM image of the negative electrode, the area ratio of carbon-coated solid graphite to the area occupied by the negative electrode active material (area occupied by carbon-coated solid graphite / area occupied by negative electrode active material) is preferably 90% or more, more preferably 99% or more, and can actually be 100%. It should be noted that the cross-sectional SEM image of the above-mentioned negative electrode is obtained according to the same steps as the SEM image when determining the "area ratio (void ratio) of the voids within the particles to the area of ​​the entire particle" in the graphite particles. The area occupied by the negative electrode active material is the area of ​​the entire particle of the negative electrode active material (also including the area of ​​the voids). It should be noted that the area ratio of carbon-coated solid graphite to the area occupied by the negative electrode active material (area occupied by carbon-coated solid graphite / area occupied by negative electrode active material) is obtained using a cross-sectional SEM image of particles containing more than 10 negative electrode active materials in one field of view. In addition, the content of carbon-coated solid graphite in all negative electrode active materials contained in the negative electrode active material layer is preferably 90% by mass or more, more preferably 99% by mass or more, and can actually be 100% by mass. In this way, by mainly using carbon-coated solid graphite as the negative electrode active material, the capacity after storage in a high temperature environment becomes larger.

[0085] The content of all negative electrode active materials in the negative electrode active material layer is preferably 60% to 99% by mass, more preferably 90% to 98% by mass. When the content of all negative electrode active materials is within the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0086] The conductive agent, binder, thickener, filler, etc. as optional components in the negative electrode active material layer can be selected from the materials exemplified in the positive electrode. However, the graphite contained in the negative electrode active material layer is not included in the conductive agent.

[0087] The content of the conductive agent in the negative electrode active material layer may be 3% by mass or less or 1% by mass or less, and the negative electrode active material layer may not contain the conductive agent.

[0088] The content of the binder in the negative electrode active material layer is preferably 0.5% by mass to 5% by mass, and more preferably 0.8% by mass to 3% by mass.

[0089] The content of the thickener in the negative electrode active material layer is, for example, preferably 0.1% by mass to 6% by mass, and more preferably 0.5% by mass to 3% by mass.

[0090] The content of the filler in the negative electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the negative electrode active material layer may be 3% by mass or less, or 1% by mass or less, or the negative electrode active material layer may not contain any filler.

[0091] The porosity of the negative electrode active material layer can be, for example, 30% to 60%. As the lower limit of the porosity, it is preferably 35%, more preferably 38%, further preferably 40%, and further preferably 42%. By making the porosity of the negative electrode active material layer above the above lower limit, the output of the non-aqueous electrolyte storage element, especially the output after storage in a high temperature environment, can be further increased. On the other hand, as the upper limit of the above porosity, it is preferably 55%, more preferably 50%, and further preferably 48%. The porosity of the negative electrode active material layer can be adjusted by the particle size of the carbon-coated solid graphite, whether or not it is pressed during manufacturing, the pressing pressure, etc.

[0092] The mass per unit area of ​​the negative electrode active material layer is not particularly limited, but is, for example, 2.0 mg / cm 2 ~12.0mg / cm 2 The lower limit of the mass per unit area of ​​the negative electrode active material layer is preferably 2.2 mg / cm 2 , more preferably 2.5 mg / cm 2 or 2.8 mg / cm 2 In some embodiments, the mass per unit area of ​​the negative electrode active material layer may be, for example, 3.0 mg / cm 2 Above, 3.5 mg / cm 2 The upper limit of the mass per unit area of ​​the negative electrode active material layer is preferably 10.0 mg / cm 2 , more preferably 8.0 mg / cm 2 or 6.0mg / cm 2 In a non-aqueous electrolyte storage device including a negative electrode active material layer having a mass per unit area within the above range, the application effect of the present configuration can be more appropriately exhibited.

[0093] Although not particularly limited, the lower limit of the ratio of the mass of carbon-coated solid graphite per unit area contained in the negative electrode active material layer to the mass of tungsten element per unit area contained in the positive electrode active material layer can be about 25. As the lower limit of the ratio, it is preferably 30, and sometimes more preferably 32, 34 or 36. On the other hand, as the upper limit of the ratio, it is preferably 100, and sometimes more preferably 80, 70, 60 or 45. In a non-aqueous electrolyte storage element in which the ratio is within the above range, the application effect of the present structure can be more appropriately exerted. The ratio of the mass of carbon-coated solid graphite per unit area contained in the negative electrode active material layer to the mass of tungsten element per unit area contained in the positive electrode active material layer can be adjusted by the content of tungsten element in the positive electrode active material, the content of carbon-coated solid graphite in the negative electrode active material, the mass per unit area of ​​the positive electrode active material layer and the negative electrode active material layer, etc.

[0094] (Isolator)

[0095] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and an adhesive formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of the shutdown function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can be used.

[0096] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products. As inorganic compounds, monomers or composites of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.

[0097] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and refers to a value measured by a mercury porosimeter.

[0098] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As polymers, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. When a polymer gel is used, there is an effect of suppressing leakage. As a separator, a porous resin film or nonwoven fabric as described above can be used together with a polymer gel.

[0099] (Non-aqueous electrolyte)

[0100] As the non-aqueous electrolyte, it can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte solution can also be used as the non-aqueous electrolyte. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0101] As nonaqueous solvent, can suitably select from known nonaqueous solvent.As nonaqueous solvent, can enumerate cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc.As nonaqueous solvent, can use the nonaqueous solvent that a part of the hydrogen atom that comprises in these compounds is replaced by halogen.

[0102] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC is preferred.

[0103] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, ethyl methyl trifluorocarbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.

[0104] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, and more preferably a cyclic carbonate and a chain carbonate are used in combination. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted and the ion conductivity of the non-aqueous electrolyte can be improved. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be suppressed to a low level. In the case of using a cyclic carbonate and a chain carbonate in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is preferably in the range of 5:95 to 50:50, for example.

[0105] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.

[0106] As lithium salts, there can be mentioned inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), lithium bis(oxalate)difluorophosphate (LiFOP), lithium salts having chlorinated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among them, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0107] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3, particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.

[0108] The non-aqueous electrolyte may contain additives other than the non-aqueous solvent and the electrolyte salt. Examples of additives include oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; and oxalic acid carbonate. Vinyl ester, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; vinyl sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, bipyridine Disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, monofluorolithium phosphate, difluorolithium phosphate, etc. These additives may be used alone or in combination of two or more.

[0109] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass relative to the mass of the entire non-aqueous electrolyte. By making the content of the additive within the above range, the capacity retention performance or cycle performance after storage in a high temperature environment can be improved, or the safety can be further improved.

[0110] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0111] As a solid electrolyte, it can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, polymer solid electrolytes, and gel polymer electrolytes.

[0112] In the case of lithium ion secondary batteries, examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.

[0113] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.

[0114] Figure 1 A non-aqueous electrolyte storage element 1 is shown as an example of a square battery. It should be noted that this figure is a perspective view of the inside of a container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.

[0115] <Configuration of power storage device>

[0116] The non-aqueous electrolyte storage element of the present embodiment can be mounted as a storage device having a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements in an automotive power source such as an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), a power source for electronic equipment such as a personal computer and a communication terminal, or a power source for power storage, etc. In this case, it is sufficient to apply the technology of the present invention to at least one non-aqueous electrolyte storage element included in the storage device.

[0117] Figure 2 An example of an electric storage device 30 is shown in which an electric storage unit 20 composed of two or more electrically connected non-aqueous electrolyte storage elements 1 is further assembled. The electric storage device 30 may include: a bus bar (not shown) electrically connecting the two or more non-aqueous electrolyte storage elements 1, a bus bar (not shown) electrically connecting the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) for monitoring the state of one or more non-aqueous electrolyte storage elements 1.

[0118] <Method for producing non-aqueous electrolyte storage element>

[0119] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and storing the electrode body and the non-aqueous electrolyte in a container. Preparing the electrode body includes: preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or winding the positive electrode and the negative electrode via a separator.

[0120] The positive electrode can be prepared by, for example, applying a positive electrode mixture paste directly or via an intermediate layer on the positive electrode substrate and drying it. The positive electrode mixture paste contains various components constituting the positive electrode active material layer such as a positive electrode active material and a dispersion medium. After the applied positive electrode mixture paste is dried, it can be pressed, etc.

[0121] The preparation of the negative electrode can be performed, for example, by applying a negative electrode mixture paste directly or via an intermediate layer to the negative electrode substrate and drying it. The negative electrode mixture paste contains various components constituting the negative electrode active material layer such as carbon-coated solid graphite and a dispersion medium. After the applied negative electrode mixture paste is dried, it can be pressed, etc.

[0122] The nonaqueous electrolyte may be stored in the container by any known method. For example, when a nonaqueous electrolyte solution is used as the nonaqueous electrolyte, the nonaqueous electrolyte solution may be injected from an injection port formed in the container and then the injection port may be sealed.

[0123] <Other embodiments>

[0124] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be added within the scope of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and in addition, a part of the structure of a certain embodiment can be replaced by the structure of other embodiments or known technology. Furthermore, a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.

[0125] In the above embodiment, the case where the nonaqueous electrolyte storage element is used as a nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) capable of charge and discharge is described, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors, or lithium ion capacitors.

[0126] Example

[0127] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0128] [Example 1]

[0129] (Production of positive electrode)

[0130] Prepare for LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The positive electrode active material of tungsten oxide is attached to the surface of the particles of O2. The content of tungsten element in the positive electrode active material relative to the metal elements other than lithium element and tungsten element is 1 mol%. The content of tungsten element in the positive electrode active material relative to the metal elements other than lithium element and tungsten element is determined by the above-mentioned determination method.

[0131] The positive electrode mixture paste is prepared using the above-mentioned positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. It should be noted that the mass ratio of the positive electrode active material, the conductive agent, and the binder is set to 93:5:2 in terms of solid content. On both sides of the aluminum foil as the positive electrode substrate, the mass per unit area (mass of the solid content) is 6 mg / cm 2 The positive electrode mixture paste is applied in a manner of , and dried. Then, roll pressing is performed to obtain a positive electrode having positive electrode active material layers stacked on both sides of the positive electrode substrate.

[0132] (Production of negative electrode)

[0133] Solid natural graphite coated with amorphous carbon as a carbonaceous material (carbon-coated solid natural graphite) was prepared as a negative electrode active material. The porosity of the carbon-coated solid graphite was 0.45%, the average particle size was 9.9 μm, and the coating amount of the carbonaceous material was 10.6% by mass. The porosity, average particle size, and coating amount of the carbonaceous material of the carbon-coated solid graphite were measured by the above-mentioned measurement method.

[0134] The negative electrode mixture paste is prepared using the above-mentioned negative electrode active material, styrene-butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. It should be noted that the mass ratio of carbon-coated solid graphite, binder, and thickener is set to 98.5:1:0.5 in terms of solid content. On both sides of the copper foil as the negative electrode substrate, the mass per unit area (mass of solid content) is 4 mg / cm 2 The negative electrode mixture paste is applied in a manner and dried. Then, roll pressing is performed to obtain a negative electrode having negative electrode active material layers stacked on both sides of the negative electrode substrate.

[0135] (Non-aqueous electrolyte)

[0136] In a solvent prepared by mixing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 30:70, the 3 LiPF6 is dissolved in a concentration of to obtain a non-aqueous electrolyte.

[0137] (Isolator)

[0138] A polyolefin microporous film was used as the separator.

[0139] (Assembly of non-aqueous electrolyte storage element)

[0140] The positive electrode, negative electrode and separator were used to obtain a wound electrode body. The electrode body was placed in a container, a nonaqueous electrolyte solution was injected and the container was sealed to obtain a nonaqueous electrolyte storage device of Example 1.

[0141] [Example 2 to Example 4 and Comparative Example 1 to Comparative Example 9]

[0142] The non-aqueous electrolyte storage devices of Examples 2 to 4 and Comparative Examples 1 to 9 were obtained in the same manner as in Example 1 except that the types of the positive electrode active material and the negative electrode active material and the coating amount of the carbonaceous material (amorphous carbon) were set as shown in Table 1. In Comparative Examples 6 to 11, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 is used as the positive electrode active material.

[0143] As the “non-solid” graphite, hollow natural graphite having a porosity of 3% and an average particle size of 9.1 μm was used.

[0144] [evaluate]

[0145] (1) Initial charge and discharge

[0146] The obtained non-aqueous electrolyte storage elements were initially charged and discharged under the following conditions. In a thermostatic chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charging end voltage of 4.10V, and then constant voltage charging was performed at 4.10V. The end condition of charging was set to a total charging time of 3 hours. Then, a rest period of 10 minutes was set. Constant current discharge was performed with a discharge current of 1.0C and a discharge end voltage of 3.0V.

[0147] (2) Determination of capacity after storage in a high temperature environment

[0148] Next, each non-aqueous electrolyte storage element is charged with a constant current of 1.0C and a charge end voltage of 4.10V in a constant temperature chamber at 25°C, and then charged with a constant voltage of 4.10V. The end condition of charging is set to a total charging time of 3 hours. Each non-aqueous electrolyte storage element after constant current and constant voltage charging is stored in a constant temperature chamber at 70°C for 20 days. Then, it is stored in a constant temperature chamber at 25°C for more than 3 hours, and constant current discharge is performed with a discharge current of 1.0C and a discharge end voltage of 3.0V. The measured values ​​of the discharge capacity of each non-aqueous electrolyte storage element are shown in Table 1 as "capacity after storage in a high temperature environment". It should be noted that in Table 1, the capacity of each example after storage in a high temperature environment is represented by a relative value when Comparative Example 10 is set to 100.

[0149]

[0150] As shown in Table 1, Examples 1 and 2, which contain a positive electrode active material containing a tungsten element and carbon-coated solid graphite coated with a carbonaceous material, and the coating amount of the carbonaceous material is 12.0% by mass or more, have a larger capacity after storage in a high temperature environment than Comparative Examples 1 to 11. This result confirms that the capacity after storage in a high temperature environment can be increased by using the positive electrode active material containing a tungsten element and the carbon-coated solid graphite with a coating amount of the carbonaceous material of 12.0% by mass or more in combination.

[0151] Industrial Applicability

[0152] The present invention can be applied to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.

[0153] Explanation of symbols

[0154] 1 Storage element

[0155] 2 Electrode body

[0156] 3 Container

[0157] 4 Positive terminal

[0158] 41 positive lead

[0159] 5 Negative terminal

[0160] 51 negative lead

[0161] 20 Storage Unit

[0162] 30 Power storage device

Claims

1. A non-aqueous electrolyte storage element comprising a positive electrode and a negative electrode, The positive electrode includes a positive electrode active material containing tungsten element, The negative electrode comprises carbon-coated solid graphite in which at least a portion of the surface of the solid graphite is coated with a carbonaceous material other than graphite; The porosity of the carbon-coated solid graphite is less than 2%, The carbon-coated solid graphite has a coating amount of the carbonaceous material of 12.0% by mass or more.

2. The nonaqueous electrolyte storage element according to claim 1, wherein The carbonaceous material is non-graphite carbon.

3. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The solid graphite is solid natural graphite.

4. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein The average particle size of the solid graphite is greater than 5 μm.

5. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The positive electrode active material further contains a transition metal element other than the tungsten element, and a lithium element. In the positive electrode active material, the content of the tungsten element relative to the metal elements other than the tungsten element and the lithium element is 0.2 mol % or more.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary battery, positive electrode and lithium secondary battery

    JP2001006676A

  • Negative pole material for lithium battery, and lithium battery

    JP2005222933A